Homer and early Greek epic : collected essays - Finkelberg, Margalit, 1947- (Trends in classics. Supplementary volumes,, 2020)
This collection includes thirty scholarly essays on Homer and Greek epic poetry published by Margalit Finkelberg over the past three decades. The topics discussed reflect the author’s research interests and represent the main directions of her contribution to Homeric studies: Homer's language and diction, archaic Greek epic tradition, Homer's world and values, transmission and reception of the Homeric poems. The book gives special emphasis to some of the central issues in contemporary Homeric scholarship, such as oral-formulaic theory and the role of the individual poet; Neoanalysis and the character of the relationship between Homer and the tradition about the Trojan War; the multi-layered texture of the Homeric poems; the Homeric Question; the canonic status of the Iliad and the Odyssey in antiquity and modernity. All the articles are revised and updated. The book addresses both scholars and advanced students of Classics, as well as non-specialists interested in the Homeric poems and their journey through centuries.